HUBUNGAN ANTARA GRIT DENGAN SUBJECTIVE WELL-BEING PADA MAHASISWA YANG BEKERJA PARUH WAKTU - Martina Dyah Ayuningtyas,; Wahyuni Kristinawati, (Journal of Innovation Research and Knowledge, 2025)
Part-time students face challenges in balancing academic and work demands, which can impact subjective well-being. This study aims to determine the relationship between grit and subjective well-being in part-time students. This study used a quantitative method with a correlational design. Grit was measured using the Grit Scale, while subjective well-being was measured using the Satisfaction With Life Scale (SWLS) and the Scale of Positive and Negative Experience (SPANE). Data analysis was carried out using the Spearman's rho correlation test which showed a significance value of 0.000 (p <0.05) and a correlation coefficient of 0.098. The results of this study indicate a significant positive relationship between grit and subjective well-being in part-time students. The higher the grit level that students have, the higher the subjective well-being they feel.